HISTORICAL DEVELOPMENT OF THE CONCEPT OF IRRATIONALITY IN ANTHROPOLOGICAL MODELS OF ECONOMIC SCIENCE - Talagaeva D.A. (Вестник Брянского государственного университета)
The article deals with the evolution of ideas about irrationality in anthropological models of economic science. The author analyzes the dynamics of the development of economic theory, starting from the classical political economy of A. Smith and D. Ricardo, and ending with modern trends, highlighting their attempts to interpret and overcome the manifestations of irrationality. Smith and D. Ricardo, and ending with modern trends, highlighting their attempts to interpret and overcome the manifestations of irrationality in human behavior. Particular attention is paid to the transformation of the concepts of rationality and irrationality in K. Marx's labor theory of value, the Keynesian concept of psychological factors in economics, and in neoliberal approaches that consider the market as a mechanism that transforms individual irrationality into collective rationality. Methodologically, the study is based on intellectual history, which interprets scientific statements in their social context, as well as on the concepts of the political economy of culture. Analyzing the conflicting moments in the development of economic science related to the problem of irrationality, the author concludes that economic theory invariably strives to model rational behavior, seeking to interpret irrational phenomena in terms of economic rationality. However, the choice of models of rationality is determined not only by scientific arguments, but also by value attitudes, which weakens the claim of economics to the status of an unbiased positive science.